Transcriptional signature of CD56bright NK cells predicts favourable prognosis in bladder cancer - Khan, Md Abdullah Al Kamran; Sedgwick, Alexander James; Sun, Yuhan; Vivian, Julian P.; Corbett, Alexandra J.; Dolcetti, Riccardo; Mantamadiotis, Theo; Mangiola, Stefano; Barrow, Alexander David (Frontiers in Immunology, 2025)
Human natural killer (NK) cells can be sub-divided into two functional subsets but the clinical significance of these CD56bright and CD56dim NK cells in anti-tumour immunity remains largely unexplored. We determined the relative abundances of gene signatures for CD56bright and CD56dim NK cells along with 3 stromal and 18 other immune cell types in the patient tumour transcriptomes from the cancer genome atlas bladder cancer dataset (TCGA-BLCA). Using this computational approach, CD56bright NK cells were predicted to be the more abundant tumour-infiltrating NK subset which was also associated with improved patient prognosis. A similar favorable survival trend was projected using gene signatures for mature myeloid dendritic cells (mDC) and CD8+ effector memory T cells (TEM) and unveiled a potential CD56bright NK-mDC-CD8+T cell crosstalk in the BLCA tumour microenvironment. Expression of transcripts encoding the activating NK cell receptors, NKG2D, NKp44, CD2, and CD160, showed positive survival trends in combination with CD56bright NK cell infiltration. Transcription factors including HOBIT, IRF3, and STAT2 were also correlated with CD56bright NK cell abundance. Additionally, a HOBIT-dependent tissue-residency program correlated with the CD56bright NK and CD8+ TEM cell signatures was found to be associated with favourable BLCA patient survival. Overall, our study highlights the significance of CD56bright NK cells in BLCA patient prognosis. Our findings facilitate a better understanding of the NK cell anti-tumour responses that may ultimately lead to the development of promising NK and T cell-based therapies for BLCA.